A Social Benefit Cost Analysis of Special Economic Zones in India: A Study of Noida SEZ. Issue 1 (March 2018) - Babita,; Bishnoi, N. K.
Special economic zones (SEZs) in India have been in news due to their usefulness vis-à-vis adverse effects on economy. A good number of opponents opine that costs incurred by SEZs outweigh the benefits. However, it cannot be denied that SEZs have played a positive role in the welfare of the economy. Thus, to examine this issue, we carried out a social benefit–cost analysis (SBCA) on Noida Special Economic Zone (NSEZ) within the context of enclave model for the period of 2009–2016. The result shows the positive net present value and benefit–cost ratio greater than one under methodological assumptions. This infers that NSEZ is contributing towards the welfare of Indian economy. One interesting findings of the study is that NSEZ is generating positive gains to economy with the absence of various market distortions which could otherwise reduce the realised benefits. Hence, need arises to eliminate such distortions from outside area of economy also to make it competitive at global level. Therefore, it can be concluded that competitiveness of the Indian economy can be enhanced with the removal of market distortions and liberalisation of rules, regulation and policies for economic development activities. Hence, the Government of India should emphasise and make regulations and policies that encourage competitiveness of the industries. JEL Classification : D04, D61, F13, H2, J01